Leading Sector Relationship To Inter-Regional Economic Growth In The Subosukawonosraten Region - Gunanto, Edy Yusuf Agung; Yasmin, Kamila (LPPM University 17 Agustus 1945 Samarinda, 2021)
This study aims to analyze the relationship between economic growth regency in Subosukawonosraten Region with leading sector approach. The linkage of leading sectors towards economic growth of other regions in the Subosukawonosraten Region determined by Multiple Linear Regression analysis. The results of the Multiple Linear Regression analysis is the most sector that has a significant influence on the other regional economic growth is sectors industry. In addition, sectors that have a significant influence on regional economic growth are real estate, agriculture, construction, information and communication, accommodation provision, trade, government and water supply, respectively.